Augmentation of interdental papilla with platelet-rich fibrin - E Ahila; R Saravana Kumar; Vineela Katam Reddy; B Pratebha; M Jananni; V Priyadharshini (Wolters Kluwer Medknow Publications, 2018)
Background: Dental esthetics has become a great concern for both dental practitioners and patients in addition to maintaining oral health. The presence of interproximal papillae between the maxillary anterior teeth is a key esthetic component. Recession of interdental papilla leads to various functional problems such as food impaction, phonetics and esthetic problems such as the formation of black triangle which poses a great challenge. Aim: This study aims to evaluate the augmentation of interdental papilla with platelet-rich fibrin. Materials and Methods: A total of 25 sites from systemically healthy individuals with papillary recession (Nordland and Tarnow class 1 and 2) were recruited in the study. Han and Takei procedure was planned and augmentation was done with platelet-rich fibrin. Various parameters such as distance from the tip of the contact point to the gingival margin, width of the keratinized gingiva, and Jemt score were measured at baseline, 3 and 6 months postoperatively. Healing index was measured at the 1st, 2nd, and 3rd week postoperatively. Results: Data collected were statistically analyzed. Mean value of distance from the contact point to the gingival margin was 4.38 mm at baseline and at 6-month postoperatively, it reduced to 0.36 mm. There was an increase in width of the keratinized gingiva which was clinically and statistically significant. Other parameters such as healing index, Jemt score, and visual analog scale (aesthetics) were also statistically significant postoperatively.